An Integrated Framework for MRO Risk Mitigation Beyond Single Dimension Classification in The Upstream Oil and Gas Sector - Andian Ari Istiningrum; Dhanang Resnamurti; Chhya Pang; Nur Ardiansah (Jurnal Manajemen Industri dan Logistik, 2026)
Upstream oil and gas companies face simultaneous MRO inventory stockouts and overstock, reflecting misallocation rather than resource scarcity. Existing classification methods – ABC (value), VED (criticality), and ADI-CV (demand pattern) – each address only one dimension, leaving residual risk that an integrated framework can eliminate. This study applies a combined ABC-VED-ADI-CV approach to 90 MRO items at an Indonesian upstream company using 12 months of transactional data and structured expert interviews. ABC identified Class A (6% of items with 80% of cost); VED classified 54% as Vital; ADI-CV found 96% exhibiting lumpy demand, confirming that conventional forecasting is inappropriate for virtually the entire portfolio. Integrating all three dimensions identified three tubing items as highly critical – Class A, Vital, and Lumpy – whose stockout triggers immediate well shutdown. The framework offers practitioners a replicable prioritisation tool for procurement, safety stock, and supplier management.